Dexmedetomidine protects PC12 cells from lidocaine-induced cytotoxicity via downregulation of Stathmin 1 - Tan Y; Bi X; Wang Q; Li Y; Zhang N; Lao J; Liu X (Dove Medical Press, 2019)
Yonghong Tan,1,* Xiaobao Bi,1,* Qiong Wang,1 Yu Li,1 Na Zhang,1 Jianxin Lao,1 Xiaoping Liu21Department of Anesthesiology, Guangzhou Women and Children’s Medical Center, Guangzhou, Guangdong 510623, People’s Republic of China; 2Department of Hematology, Guangzhou Women and Children’s Medical Center, Guangzhou, Guangdong 510623, People’s Republic of China*These authors contributed equally to this workBackground: Understanding of lidocaine-induced neurotoxicity is not complete, resulting in the unsuccessful treatment in some clinical settings. Dexmedetomidine (DEX) has been shown to alleviate lidocaine-induced neurotoxicity in our previous cell model. However, the rationale for DEX combined with lidocaine to reduce lidocaine-induced neurotoxicity in the clinical setting remains to be further clarified in the detailed molecular mechanism.Methods: In this study, we established a cellular injury model by lidocaine preconditioning. Cell Counting Kit-8 (CCK-8) and 5-ethynyl-2ʹ-deoxyuridine (EdU) proliferation assay kit were used to analyze cell proliferation. Cell apoptosis was measured by flow cytometry and Hoechst 33342 staining. Cell cycle progression was detected by flow cytometry. The protein expression levels were detected by Western blotting and immunofluorescence staining.Results: Our results showed that DEX dose-dependently restored impaired proliferation of PC12 cells induced by lidocaine，as reflected by the increased cell viability and EdU positive cells, which were consistent with the decreased expression of tumor suppressor protein p21 and increased expression of cell cycle-related cyclin D1 and CDK1. In addition, DEX dose-dependently reduced apoptotic PC12 cells induced by lidocaine，as reflected by the decreased expression of apoptosis-related Bax, caspase-3 and caspase-9 and increased expression of anti-apoptotic Bcl-2 compared to the cells only treated with lidocaine. Mechanistically, with gain-or-loss-of-function of STMN1, we showed that DEX-mediated neuroprotection by lidocaine-induced damage is associated with downregulation of STMN1 which might be an upstream molecule involved in regulation of mitochondria death pathway.Conclusion: Our results reveal that DEX is likely to be an effective adjunct to alleviate chronic neurotoxicity induced by lidocaine.Keywords: dexmedetomidine, lidocaine, STMN1, neurotoxicity, proliferation, apoptosis